Pengaruh Parameter Proses 3D Printing Tipe Fdm Terhadap Hasil Transparansi Pada Filamen ABS (Acetonitrile Butadiene Stryene) - Indun, Indun; Juanda, Juanda; Pristiansyah, Pristiansyah (Jurnal Inovasi Teknologi Terapan, 2024)
(3D) Printing technology is one of the new innovations in manufacturing. Utilizing additive manufacturing principles to convert 3D computer-aided design (CAD) data directly into physical prototypes, 3D printing technology works by building layer by layer to form prototypes. Fused Deposition Modeling (FDM) technology is a printing procedure used to print products using fibrous materials and the printed products have perfect geometric characters. In the research conducted using transparent type ABS filament with a diameter of 1.75. with Ender 3 Max FDM 3D printing machine. Nozzle temperature (250, 255, 260 bed temperature (85 90 95), print speed (50 55 60) using the taguci method in 3D printing minitab software to find the transparency of production which will be measured using a lux meter tool. which is where the average research results of the low transparency test are the 1st sample, which is an average of 47. the optimal value is at temperature temperature 250, bed temperature 85, print speed 50. with the mean plot value of Nozzle Temperature (102.33), Build Plate Temperature (101.00), Print speed (76.89).